(untitled) (International Journal of Engineering and Computer Science, 2015)
Blue tooth wireless technology is vastly different from 802.11b wireless local area network technology. Not only is it significantly slower than 802.11b products, but also it’s also completely incompatible with them. To better understand this, let’s take a look at what Blue tooth technology is and what exactly it was designed to do. Bluetooth is a telecommunications industry specification that describes how mobile phones, computers, and personal digital assistants can be easily interconnected using a short-range wireless connection. Bluetooth products achieve this by placing a small, inexpensive radio transmitter/receiver module in each electronic device. This module acts as the physical medium to connect these devices and also provides the necessary communication protocols needed for these devices to successfully transmit data.